2010
DOI: 10.1111/j.1460-2695.2010.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue assessment of welded structures: practical aspects for stress analysis and fatigue assessment

Abstract: A B S T R A C T Analysis of welded structures still remains a challenge for the analyst and in fact cannot be considered as fully solved for practical applications. For many years, a large international aggregation of researchers has developed methods to assess fatigue behaviour of welded structures. Nowadays many suggestions and methods exist to estimate fatigue life of welded structures with respect to nominal, structural, notch stress or fracture mechanics approaches. All of them are still under improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…. The presence of a finite radius at the otherwise sharp notch removes the stress singularity at sharp re‐entrant corners . The pioneering studies by Radaj have demonstrated that the fictitious radius at the notch of welded steel joints has a value of 1 mm, based on the microstructural support theory proposed by Neuber .…”
Section: Introductionmentioning
confidence: 99%
“…. The presence of a finite radius at the otherwise sharp notch removes the stress singularity at sharp re‐entrant corners . The pioneering studies by Radaj have demonstrated that the fictitious radius at the notch of welded steel joints has a value of 1 mm, based on the microstructural support theory proposed by Neuber .…”
Section: Introductionmentioning
confidence: 99%
“…It is similar to a quadratic surface stress extrapolation used in the context of structural stress approaches to the fatigue assessment of welds (e.g. 31 ). Another option -not explicitly addressed in EN 13445-3 would be a path linearization with respect of strains across the wall thickness (volumetric FE model presumed).…”
Section: General Evaluation By Elastic-plastic Analysismentioning
confidence: 99%
“…The peak strain values die out rapidly and thus the surface strains at the hot spot locations deliver lower resulting strain values. This is a general problem of surface extrapolation methods 31 . The courses of stresses/strains between the extrapolation points and the hot spot have to be verified with respect of plausibility and applicability of the extrapolation procedure 31 .…”
Section: Heat Exchanger Tube Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…Haftirman, et al [4], and Rother and Rudolph [5] were of the opinion that Fatigue is a failure mechanism where the component fails after a period of time in service and also sees a repetitive cyclic stress.…”
Section: Introductionmentioning
confidence: 99%